Auditory Proprioceptive Integration: Effects of Real-Time Kinematic Auditory Feedback on Knee Proprioception - Ghai, Shashank; Schmitz, Gerd; Hwang, Tong-Hun; Effenberg, Alfred O. (Frontiers in Neuroscience, 2018)
The purpose of the study was to assess the influence of kinematic real-time auditory feedback on knee proprioceptive re-positioningon. Thirty healthy participants were randomly allocated to control (n=15), and experimental group I (15). The participants performed an active knee-repositioning task using their dominant leg, with/without additional real-time auditory feedback where the frequency was mapped toin a convergent manner to two 2 different target angles (40° and 75°). Statistical analysis revealed significant enhancement in knee re-positioning -proprioception acaccuracy for the constant and absolute error with real-time auditory feedback, within and across the groups. Besides this convergent condition, we established a second divergent condition. Here, a in terms of a slight step -wise modulation transposition of theof frequency-mapping was performed to explore if whether a systematic tuning of thebetween auditory-proprioceptive repositioning will become evident. Here, noexists. No significant effects were recognizable identified in the this divergent auditory-proprioceptive feedback condition. An additional experimental group II (n=20) was further included. Here, we investigated the influence of a larger where a larger magnitude and directional change of step-wise modulation transposition of the frequency-mapping was applied. In a first step, results confirm the findings of group experiment I. FurtherMoreover, significant effects on knee auditory-proprioception repositioning were evident when divergent real-time auditory feedback was applied. During the step-wise transposition participants showed systematic modulation of knee movements in the opposite direction of transposition. This study is the first to confirm the auditory-proprioceptive substitution hypothesis. We confirm that knee re-positioning accuracy can be enhanced with concurrent application of real-time auditory feedback and that knee re-positioning can modulated in a goal-directed manner with real-time kinematic auditory feedbackwith step- wise transposition of frequency. Clinical implications are discussed with respect to proprioception joint position sense in rehabilitation settings.